Comparison of arthroscopic versus open surgery on external snapping hip caused by gluteal muscle contracture. Issue 2 (March 2018) - Dai, Zhu; Chen, Zhiwei; Liao, Ying; Tang, Zhengwu; Cui, Juncheng
Purpose: To compare the outcomes of contracture release by arthroscopic versus open surgical approach in patients with external snapping hip (ESH) caused by gluteal muscle contracture (GMC). Methods: Medical records of patients with ESH due to GMC who underwent open surgery (n = 44) or arthroscopic surgery (n = 48) between October 2008 and October 2014 were reviewed. Patients were followed up at 1, 3, 12, and 24 months postoperatively. Operation time, incision length, postoperative pain, postoperative complication rate, and recurrence rate were compared between the 2 groups. Hip adduction, and Harris Hip Scores (HHS) at 1 and 2 years postoperatively were compared between the groups and with preoperative data. Results: Mean operation time did not differ between the 2 groups (p>0.05). The arthroscopic surgery group had smaller incisions (p<0.05), less postoperative pain (p<0.05), lower complication rates (p<0.05) than did the open surgery group. The recurrence rates were similar for the 2 groups (p>0.05). Hip adduction, and HHS 1 year and 2 years postoperatively were significantly better postoperatively than they had been preoperatively for both groups (all p<0.01), and were similar for the 2 groups (all p>0.05). Conclusions: Arthroscopic release of contracture tissue is a safe and effective approach for the treatment of ESH caused by GMC, with the advantages of small scars, less postoperative pain, fewer complications compared with open surgery.